1994
DOI: 10.1007/bf00218913
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic investigations of the mechanism of tumourigenesis in von Hippel-Lindau disease: analysis of allele loss in VHL tumours

Abstract: Von Hippel-Lindau (VHL) disease is a dominantly inherited familial cancer syndrome characterised by the development of retinal and central nervous system haemangioblastomas, renal cell carcinoma (RCC), phaeochromocytoma and pancreatic tumours. The VHL disease gene maps to chromosome 3p25-p26. To investigate the mechanism of tumourigenesis in VHL disease, we analysed 24 paired blood/tumour DNA samples from 20 VHL patients for allele loss on chromosome 3p and in the region of tumour suppressor genes on chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(55 citation statements)
references
References 25 publications
0
54
0
1
Order By: Relevance
“…Initially it was noted that phenotypes in Caucasian VHL families paralleled Japanese families for most mutations . Later studies by Yoshida et al [2000] found that mutations p.Arg113Ter, p.Gln132Ter, p.Leu158Val, and p.Cys162Tyr, which were previously associated with VHL Type 1 in Western cultures [Crossey et al, 1994a;Glavac et al, 1996;Maher et al, 1996;Zbar et al, 1996], were associated with VHL Type 2 in Japanese families [Clinical Research Group for VHL in Japan, 1995;Yoshida et al, 2000]. A study of 15 Korean patients showed the majority of VHL Type 1 mutations were nonmissense mutations, similar to those found in Japan and Western cultures [Cho et al, 2009].…”
Section: Ethnic Diversitymentioning
confidence: 68%
“…Initially it was noted that phenotypes in Caucasian VHL families paralleled Japanese families for most mutations . Later studies by Yoshida et al [2000] found that mutations p.Arg113Ter, p.Gln132Ter, p.Leu158Val, and p.Cys162Tyr, which were previously associated with VHL Type 1 in Western cultures [Crossey et al, 1994a;Glavac et al, 1996;Maher et al, 1996;Zbar et al, 1996], were associated with VHL Type 2 in Japanese families [Clinical Research Group for VHL in Japan, 1995;Yoshida et al, 2000]. A study of 15 Korean patients showed the majority of VHL Type 1 mutations were nonmissense mutations, similar to those found in Japan and Western cultures [Cho et al, 2009].…”
Section: Ethnic Diversitymentioning
confidence: 68%
“…VHL is considered a classical tumor suppressor gene in the sense that, in accordance with Knudsons two-hit model, biallelic inactivation is usually required for tumorigenesis (Knudson 1971(Knudson , 1996. Loss of heterozygosity (LOH) of the wild-type allele is frequent in VHL-associated tumors, including PCCs (Crossey et al 1994), and hypermethylation of the wild-type allele as an alternative mechanism of gene inactivation has also been reported (Herman et al 1994, Prowse et al 1997, although not in PCCs (Bender et al 2000). Disease-causing mutations in VHL can be missense, nonsense, as well as deletions and insertions (indels), with missense mutations being more frequent in families with PCC/PGL (Woodward & Maher 2006).…”
Section: Ret-associated Pccs and Pglsmentioning
confidence: 99%
“…Germ line mutations or loss of the von Hippel-Lindau (VHL) 1 gene predispose to a rare hereditary cancer syndrome characterized by the development of renal cell carcinoma (RCC) as well as other tumors including central nervous system hemangioblastomas, pheochromocytomas, and retinal angiomas (1)(2)(3)(4)(5)(6)(7)(8). The VHL gene, which maps to chromosome 3p25-p26, is also commonly mutated or silenced in sporadic RCC and, like p53 and Rb, fulfills Knudsen's criteria for a tumor suppressor gene (5,6,9,10).…”
mentioning
confidence: 99%